Unveiling Effective Student Communication Strategies for English Mastery: Mengungkap Strategi Komunikasi Siswa yang Efektif untuk Penguasaan Bahasa Inggris - Aqida , Siti Nur; Mandarani, Vidya (Universitas Muhammadiyah Sidoarjo, 2024)
This research explores how communication strategies assist seventh-grade students in overcoming English-speaking challenges at SMP Muhammadiyah 9 Boarding School Tanggulangin, Sidoarjo, Indonesia. Using qualitative methods, including observation and semi-structured interviews, the study identifies various strategies employed by students, such as avoidance, paraphrase, borrowing, appeal for assistance, and mime, with language switch in borrowing being predominant. Findings indicate a positive impact of these strategies on students' ability to achieve communication goals. This study underscores the importance of optimizing communication strategies to enhance English proficiency and facilitate effective communication in language learning environments. Highlight: Diverse Strategies Identified: Students use varied methods to tackle English-speaking difficulties. Dominant Technique: Language switch in borrowing prevails among student strategies. Effective Impact: Communication strategies positively enhance student English proficiency and communication success. Keywoard: Communication Strategies, English Proficiency, Seventh-Grade Students, Qualitative Research, Language Learning.